A risk-based treatment strategy for non-rhabdomyosarcoma soft-tissue sarcomas in patients younger than 30 years (ARST0332): a Children's Oncology Group prospective study. Issue 1 (January 2020) - Spunt, Sheri L; Million, Lynn; Chi, Yueh-Yun; Anderson, James; Tian, Jing; Hibbitts, Emily; Coffin, Cheryl; McCarville, M Beth; Randall, R Lor; Parham, David M; Black, Jennifer O; Kao, Simon C; et al.
Summary: Background: Tumour grade, tumour size, resection potential, and extent of disease affect outcome in paediatric non-rhabdomyosarcoma soft-tissue sarcoma (NRSTS), but no risk stratification systems exist and the standard of care is poorly defined. We developed a risk stratification system from known prognostic factors and assessed it in the context of risk-adapted therapy for young patients with NRSTS. Methods: In this prospective study, eligible patients enrolled in 159 hospitals in three countries were younger than 30 years, had a Lansky (patients ≤16 years) or Karnofsky (patients >16 years) performance status score of at least 50, and a new diagnosis of a WHO (2002 criteria) intermediate (rarely metastasising) or malignant soft-tissue tumour (apart from tumour types eligible for other Children's Oncology Group studies and tumours for which the therapy in this trial was deemed inappropriate), malignant peripheral nerve sheath tumour, non-metastatic and grossly resected dermatofibrosarcoma protuberans, undifferentiated embryonal sarcoma of the liver, or unclassified malignant soft-tissue sarcoma. Each patient was assigned to one of three risk groups and one of four treatment groups. Risk groups were: low (non-metastatic R0 or R1 low-grade, or ≤5 cm R1 high-grade tumour); intermediate (non-metastatic R0 or R1 >5 cm high-grade, or unresected tumour of any size or grade); or high (metastatic tumour). The treatment groups were surgery alone, radiotherapy (55·8 Gy), chemoradiotherapy (chemotherapy and 55·8 Gy radiotherapy), and neoadjuvant chemoradiotherapy (chemotherapy and 45 Gy radiotherapy, then surgery and radiotherapy boost based on margins with continued chemotherapy). Chemotherapy included six cycles of ifosfamide 3 g/m 2 per dose intravenously on days 1–3 and five cycles of doxorubicin 37·5 mg/m 2 per dose intravenously on days 1–2 every 3 weeks with sequence adjusted on the basis of timing of surgery or radiotherapy. The primary outcomes were event-free survival, overall survival, and the pattern of treatment failure. Analysis was done per protocol. This study has been completed and is registered with ClinicalTrials.gov, NCT00346164 . Findings: Between Feb 5, 2007, and Feb 10, 2012, 550 eligible patients were enrolled, of whom 21 were treated in the incorrect group and excluded from this analysis. 529 evaluable patients were included in the analysis: low-risk (n=222), intermediate-risk (n=227), high-risk (n=80); surgery alone (n=205), radiotherapy (n=17), chemoradiotherapy (n=111), and neoadjuvant chemoradiotherapy (n=196). At a median follow-up of 6·5 years (IQR 4·9–7·9), 5-year event-free survival and overall survival were: 88·9% (95% CI 84·0–93·8) and 96·2% (93·2–99·2) in the low-risk group; 65·0% (58·2–71·8) and 79·2% (73·4–85·0) in the intermediate-risk group; and 21·2% (11·4–31·1) and 35·5% (23·6–47·4) in the high-risk group, respectively. Risk group predicted event-free survival and overall survival (p<0·0001). No deaths from toxic events during treatment were reported. Nine patients had unexpected grade 4 adverse events (chemoradiotherapy group, n=2; neoadjuvant chemoradiotherapy group, n=7), including three wound complications that required surgery (all in the neoadjuvant chemoradiotherapy group). Interpretation: Pre-treatment clinical features can be used to effectively define treatment failure risk and to stratify young patients with NRSTS for risk-adapted therapy. Most low-risk patients can be cured without adjuvant therapy, thereby avoiding known long-term treatment complications. Survival remains suboptimal for intermediate-risk and high-risk patients and novel therapies are needed. Funding: National Institutes of Health, St Baldrick's Foundation, Seattle Children's Foundation, American Lebanese Syrian Associated Charities.